Explaining Canada–US differences in attitudes toward the role of government: a test of S.M. Lipset's 'Continental Divide'. Issue 4 (2nd October 2018) - Baxter-Moore, Nick; Eagles, Donald Munroe; Berrada, Ibrahim; Chernomorchenko, Oleksandr; Coleman, Paul D.; Gaskin, Kelly; Hatch, Karey; Hilimoniuk, Craig; Morris, Patrick
ABSTRACT: For decades scholars have engaged in a lively debate about the distinctiveness of Canadian and American value systems. Lipset (1990) argues that divergent responses to the American Revolution led Canada to embrace Tory values of 'peace, order, and good government' while Americans pursued classical liberal values of 'life, liberty, and the pursuit of happiness'. Other scholars question the extent, or even the existence, of the differences Lipset describes. Using surveys of students from Canadian and American universities close to the Canada–US border, we identify compelling support for Lipset's hypothesised differences on the role of government in the least likely setting imaginable.